Lejonet från Norden, hindrar alla morden? - En kriminologisk fallstudieanalys av Gustav Adolfs torg i Göteborg - Persson, Sofia; Granrud, Lisa (2022)
Aims and objectives: The aim of this thesis is to contribute with an increased knowledge of how systematic crime prevention work can be practiced in inner-city environments. By analyzing conditions and obstacles of crime and insecurity problems at Gustav Adolf's square, a square in central Gothenburg, success factors related to the place have been identified. The thesis can also contribute to a theoretical development as well as inspire future research by testing the validation of the ORCA model. Method and data: The thesis is a case study using mixed methods. The primary data are observations of Gustav Adolf's square, semi-structured interviews with representatives in the police and emergency services, unstructured interviews with field-workers, security guards and structured interviews with individuals passing by the square. Secondary data are official documents and statistics from the police and Göteborgs Stad. The empirical data have been analyzed using a pattern matching technique with themes derived from the ORCA model Results: The descriptive results of the study show that Gustav Adolf's square has a low crime rate. The ORCA model suggests this can be explained by a combination of low degree of crime-attracting elements and low levels of informal social control. Recommendations on how systematic crime prevention work can be practiced are presented. Furthermore, it is noted that the ORCA model, to some extent, disregards an important variable that can also explain the level of crime at places, i.e. how the place is used, whereupon a development of the ORCA model is suggested